Pathways towards new criminalisation: the case of stalking in Portugal - Ferreira, Célia (2018)
Stalking, which is a form of interpersonal violence, has been increasing and has a significant impact on affected victims. However, despite established scientific consensus, the juridical–legal system, specifically in Europe, is still extremely asymmetric. Portugal, compelled by scientific data and the Istanbul Convention, was the most recent country to approve specific legislation against stalking. In this critical review, we describe the previous national situation and provide examples from other countries to elucidate the trajectory of the recent criminalisation process, analyse the existing legal content and reflect upon the implications and challenges associated with this legal progression.